Kawaii Culture in Japan: A Bibliometric Analysis and Text Mining Approach Based on Pop-Cultural Diplomacy and Transmission into Global Values - Hiroko Oe; Max Weeks (Budapest International Research and Critics University, 2020)
This research aims to develop a discussion framework for Kawaii cultural study based on a bibliometric analysis and text mining approach. First, a bibliometric analysis is conducted on literature pertaining to ‘Kawaii and Japanese pop culture’ extracted from the academic database; from this standpoint, the current research topics in the field of Kawaii study are discussed. Second, we aim to provide direction for future research by mining the text data disseminated by three special exhibitions launched by Japanese museums on the theme of ‘Japanese Kawaii culture’ and planned by Kawaii cultural experts and curators. From the results of these two studies, the present research develops a discussion framework containing key dimensions and factors for researchers in this field of study.